An innovative approach of mixed enzymatic venture for 2G ethanol production from lignocellulosic feedstock. (1st March 2020) - Rajak, Rajiv Chandra; Banerjee, Rintu
Graphical abstract: Highlights: An enzymatic approach for lignocellulosics bioprocessing was attempted. Mixed enzymes application reduced the entire process time appreciably. Significant lignin degradation was observed due to laccase action. Enzymes efficacy were reflected through biomass porosity, XRD and SEM analysis. Enzymatic venture for Kans grass bioprocessing improves ethanol yield. Abstract: Time is an important factor for bioenergy and bio-product producing industries. Longer process/fermentation times are the major hurdles in making the process more cost effective for any desired product. Integration of different process units were usually carried out to minimize the entire processing time. However, apart from consolidation, microbial adaptation and biomass pretreatment methods plays an important role during product generation. Microorganisms normally take longer time to adapt to the surrounding environment, which certainly affect the entire processing time. Thus, the present work was framed to use mixture of crude and low titre enzymes for lignin degradation and holocellulose hydrolysis followed by fermentation in a single unit to produce second generation ethanol from Kans grass. In the present study, an enzymatic venture was attempted to delignify the recalcitrant lignin molecule and simultaneously hydrolyse the biomass for enhanced sugars generation followed by ethanol production in a common platform. The entire ethanol production process has been optimized through response surface methodology that resulted in 59.96 g/L of ethanol within 24 h. The biomass porosity analysis in terms of surface area, pore size and pore volume of the fermented biomass were found to be decreased that indicates effective action of applied enzymes. Structural characterisation of the fermented biomass showed an extensive surface distortion that revealed the combined action of delignifying and saccharifying enzymes. X-ray diffraction analysis indicates reduced biomass crystallinity after fermentation, which inferred that para-crystalline and crystalline cellulose were utilized maximally for ethanol production. Thus, the results obtained in the present study substantiate the feasibility of the mixed enzymes application in bioprocessing of Kans grass for second generation ethanol production.